ОСОБЛИВОСТІ ПАРАДИГМИ ОСВІТНЬОЇ СИСТЕМИ ГАЛУЗЕВОГО ПІДПОРЯДКУВАННЯ ДЛЯ ПРОМИСЛОВОСТІ - Шандиба, Олена (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Проведено дослідження існуючої та обґрунтування нової парадигми освітньої системи галузевого підпорядкування для промисловості України. Відзначено, що ключову роль у визначенні ідеології, напрямів діяльності та удосконалення освітньої системи відіграє її парадигма – інформаційний інтегратор системи. Проведено аналіз сучасного стану освітньої системи галузевого підпорядкування для промислового комплексу України. Відображено, що ведучим пріоритетом сучасної парадигми загальної освіти стає саморозвиток особистості у вільних формах діяльності. Відзначено, що особливості загальноосвітньої парадигми – спільні основні складові парадигми загальної освіти та освіти галузевого підпорядкування. Підкреслено, що сучасні навчальні заклади післядипломної освіти повинні стати «закладами творчості». Показано, що парадигма повинна бути оптимізована, виходячи з системно-кібернетичного підходу з врахуванням основних, допоміжних та управлінських функцій системи. Проведено исследование существующей и обоснование новой парадигмы образовательной системы отраслевого подчинения для промышленности Украины. Отмечено, что ключевую роль в определении идеологии, направлений деятельности и совершенствования образовательной системы играет ее парадигма – информационный интегратор системы. Проведен анализ современного состояния образовательной системы отраслевого подчинения для промышленного комплекса Украины. Отражено, что ведущим приоритетом современной парадигмы общего образования становится саморазвитие личности в свободных формах деятельности. Отмечено, что особенности общеобразовательной парадигмы – общие основные составляющие парадигмы общего образования и образования отраслевого подчинения. Подчеркнуто, что современные учебные заведения последипломного образования должны стать «заведениями творчества». Показано, что парадигма должна быть оптимизирована, исходя из системно-кибернетического подхода с учетом основных, вспомогательных и управленческих функций системы. The existing paradigm of educational system subordinate to manufacturing sectors and intended for industry of Ukraine is analyzed and the new paradigm is substantiated. The article proves that the relevance of the paradigm improvement is enhanced due to acceleration of scientific-technical progress, shortening of equipment life cycles and increase of variety of practically applied technologies. It is mentioned that the key role in determination of ideology, lines of activity and improvement of educational system is played by its paradigm – informational integrator of the system. The current state of educational system subordinate to manufacturing sectors and intended for industrial complex of Ukraine is analyzed. It is shown that selfevolution of a person by involvement in free types of activity becomes the top priority of the current paradigm of general education. It is mentioned that educational system subordinate to manufacturing sectors can be improved by system change of mechanisms of influence on trainees as well as use of capabilities of supersystem consisting of institutions, which employ the trained staff, norms of material and moral influence, legislative and ethic norms. It is mentioned that peculiarities of educational paradigm are the main integral parts common for general education and education subordinate to manufacturing sectors. It is emphasized that the modern post-graduate educational institutions should be ‘institutions of creative work’. The article proves that the paradigm should be optimized on the basis of system-cybernetic approach considering the main, auxiliary and managerial functions of the system.